Effect of Planting Media Composition and Probiotics of Effective Microorganisme 4 Application on the Production of Oyster Mushroom (Pleurotus Ostreatus) - Abdul Rahmi; Noor Jannah; Rudy Apriyanto (Budapest International Research and Critics University, 2022)
The purpose of this research are: (1) to determine the effect of planting media composition and probiotics effective microorganisme 4 (EM4) application as well as its interaction on the production of oyster mushroom, and (2) to find the proper of planting media composition and the probiotics EM4 concentration to obtain the optimal production of oyster mushrooms. The research conducted at Barong Tongkok Village, Barong Tongkok Sub District of West Kutai Regency. It began from April to November 2018 commencing from baglog preparation until the end of observation. The research used a completely randomized design (CRD) factorial 4 x 4 with 5 replications. The first factor was the composition of the planting media (M) with 4 levels of treatment, namely the percentage of different composition of mushroom growing media, they are sawdust: bran: cornflour: lime: SP-36; namely m1 = 75:21:1:2:1; m2 = 80:17:1:2:0; m3 = 85:12:0.5:1.5:1; and m4 = 90:8:0.5:1.5:0. The second factor was the application of probiotics EM4 with 4 levels of treatment, namely: p0 = no probiotics, p1 = 5 ml l-1 water; p2 = 10 ml l-1 water, and p3 = 15 ml l-1 water. The research results revealed that : (1) the mushroom planting media composition affected very significantly on the mushroom mycelium growth (at 14, 18, 22, 26, 30, 34, 38 and 42 days after inoculation (HSI), age at harvest, mushroom production, and biology efficiency ratio (REB). The highest production of oyster mushrooms attained at the m1 treatment, namely 533.0 g baglog-1; in reverse, the lowest one attained at the m4 treatment, namely 406.3 g baglog-1; (2) the application of EM4 on the mushroom growing media affected significantly to very significantly affect on the mushroom mycelium growth (at 18, 38 and 42 HSI), age at harvest, mushroom production and REB, but it was not significantly affect on the mushroom mycelium growth at 14, 22, 26 and 30 HIS. The highest production of oyster mushrooms attained at the p2 treatment, namely 562.0 g baglog-1, meanwhile the lowest one was attained at the p0 treatment with only 406.3 g baglog-1; (3) the interaction effect between the mushroom growing media and EM4 application was very significantly effect on the REB, but it was not significant on the mushroom mycelium growth at all days observed, age at harvest, and mushroom production.